1999
DOI: 10.1128/iai.67.2.539-545.1999
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of the Safety and Immunogenicity of a New CTXΦ-Negative, Hemagglutinin/Protease-Defective El Tor Strain as a Cholera Vaccine Candidate

Abstract: Vibrio cholerae 638 (El Tor, Ogawa), a new CTXΦ-negative hemagglutinin/protease-defective strain that is a cholera vaccine candidate, was examined for safety and immunogenicity in healthy adult volunteers. In a double-blind placebo-controlled study, no significant adverse reactions were observed in volunteers ingesting strain 638. Four volunteers of 42 who ingested strain 638 and 1 of 14 who received placebo experienced loose stools. The strain strongly colonized the human small bowel, as evidenced by its isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Finally, our observations suggest an explanation for why HA /P-positive but not HA /P-negative V. cholerae elicit mild diarrhoea in vaccine studies (Benitez et al, 1999).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Finally, our observations suggest an explanation for why HA /P-positive but not HA /P-negative V. cholerae elicit mild diarrhoea in vaccine studies (Benitez et al, 1999).…”
Section: Resultsmentioning
confidence: 59%
“…Later, we found that V. cholerae haemagglutinin/protease (HA /P) is also a cytotoxin and suggested that it might be responsible for the remaining diarrhoea genicity of the vaccine strains (Wu et al, 1996). Indeed, Benitez et al (1999) have shown recently that a V. cholerae vaccine strain in which not only the known enteric toxins of V. cholerae, i.e. CT, ZOT and Ace, but also HA /P had been attenuated and did not cause any adverse reaction in test subjects.…”
Section: Introductionmentioning
confidence: 99%
“…HapA also causes cell rounding, loss of the barrier function of the epithelial layer, and, ultimately, detachment of the cells under tissue culture conditions 13,14 . Consistent with these in vitro activities, a 10-fold increase in the 50% lethal dose (LD 50 ) in the absence compared to the presence of the HapA protease for V. cholerae strains that otherwise lack cholera toxin was reported 15 . It was therefore suggested that HapA participates in the attachment as well as in the detachment of V. cholerae from the gut epithelium 12,16 and that tissue destruction through HapA-mediated cleavage of surface-exposed proteins may contribute to fluid leakage and the stimulation of proinflammatory responses 7 .…”
mentioning
confidence: 62%
“…We speculated, therefore, that this HapA-mediated disintegration of HlyA might have evolved to allow V. cholerae to maximize its growth output within this intra-amoebal replication niche by avoiding the premature death of its host. Notably, the HapA protease is considered a minor virulence factor that contributes to disease outcome in animal models of cholera 15,45 , along with HlyA itself, as described above. In this study, we did not observe any obvious phenotype for V. cholerae strains lacking HlyA with respect to their ability to first colonize and then escape the amoebal contractile vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implicit release of living bacteria into the environment continues to be a cause of concern worldwide. The El Tor Ogawa live cholera vaccine candidate strain 638 was recently demonstrated to be well tolerated and immunogenic in Cuban volunteers (5), as was CVD103HgR in North American volunteers (32). Inactivation of the thyA gene has been proposed as a biological containment tool for microorganisms intended to be released into the environment (23).…”
mentioning
confidence: 99%